Techno-economic Analysis of a Stand-alone Photovoltaic-Diesel Hybrid System for Rural Area in Sarawak - Harmen, M.; Julai, N.; Othman, A. K.; Aznan, H.; Kulanthaivel, G. (International Journal of Integrated Engineering, 2020)
Photovoltaic hybrid power generation is an alternative solution for supplying electricity to rural areas, especially in Sarawak, Malaysia, where grid connection is almost impossible due to the cost and geographic location. Diesel generator systems are still used by local communities in these remote areas, and the implementation of photovoltaic diesel hybrid systems can reduce dependency on diesel generator units. The work presented in this paper explores the possibility of integrating solar energy resource with diesel generator to meet the load demand of rural communities in Sarawak. In further detail, the configuration and size of the PV-diesel system are analyzed in based on the lowest net present cost (NPC) and the cost of electricity (COE). The analysis is based on mathematical modeling and simulation using Hybrid Optimization Model for Electric Renewables (HOMER) software. Eight different configurations of two energy resources-photovoltaic panels and diesel generators-are studied and compared. The option with the highest optimization values is considered to be the most feasible electrification solution for the particular rural area. The outcomes of the analysis show that the PV-diesel hybrid configuration proves to be more cost-effective compared to an existing generator-based system in that it reduces fuel dependency and has the lowest NPC and COE among all configurations studied.